Soil fertility dynamics under varying land use systems in Jatiarjo Village, Prigen Sub-district, Pasuruan, Indonesia - PURNOMO EDI SASONGKO; WANTI MINDARI; MUHAMMAD RIZKY ROMADHON; HAMMADA HIDAYATURRACHMAN (Asian Journal of Agriculture, 2026)
Abstract. Sasongko PE, Mindari W, Romadhon MR, Hidayaturrachman H. 2026. Soil fertility dynamics under varying land use systems in Jatiarjo Village, Prigen Sub-district, Pasuruan, Indonesia. Asian J Agric 10 (2): g100201. https://doi.org/10.13057/asianjagric/g100201. Variations in land use, geographical conditions, and land management practices highly influence soil fertility. This study evaluated the soil fertility status of three dominant land-use systems-mixed garden, shrubland, and moorland in Jatiarjo Village, Prigen Sub-district, Pasuruan District, East Java, Indonesia. Three land use units, including mixed garden, shrubland, and moorland, were assessed using the Soil Fertility Index (SFI). Soil sampling was a random sampling method at a 0-20 cm depth, with 7 points in each land unit. Soil samples were analyzed for soil. Chemical characteristics included pH, organic carbon (C), total nitrogen (N), available phosphorus (P), exchangeable potassium (K), Cation Exchange Capacity (CEC), Base Saturation (BS), Aluminum Saturation (AS), and soil texture. Minimum Soil Fertility Indicators (MSFI) were identified using Pearson correlation and Principal Component Analysis (PCA), and the Soil Fertility Index (SFI) was calculated accordingly. Soil pH ranged from 5.15-6.44, organic C from 2.20-11.60%, total N from 0.12-1.06%, available P from 0.60-18.54 ppm, and exchangeable K from 0.09-0.15 μg/100 g. CEC was 24.44-43.97 me/100 g, while BS remained very low (5.31-10.01%). SFI indicated medium fertility across all land uses, averaging 0.62 in mixed gardens, 0.61 in shrublands, and 0.58 in moorlands. Higher SFI in mixed gardens reflected greater organic matter inputs, whereas lower fertility in moorlands was linked to minimal organic inputs and more intensive cultivation. This study highlights the significance of organic matter application and land conservation practices in sustaining and enhancing soil fertility, and also provides a scientific basis for targeted land management to sustain soil productivity in upland agroecosystems.